Academic Paper-Writing Performance of First-Year Early Childhood Islamic Education Students - Wina Santyani; Khamim Zarkasih Putro; Siti Zubaedah (Kognisi: Jurnal Ilmu Keguruan, 2026)
Academic writing is a foundational practice through which university students learn to organize knowledge, construct arguments, use evidence, and participate in disciplinary communities. This study examined the quality of academic paper writing produced by first-semester students in the Early Childhood Islamic Education (PIAUD) program at Universitas Islam Negeri Sunan Kalijaga, Indonesia. A descriptive document-analysis design was used, combining quantitative scoring with qualitative interpretation. The unit of analysis comprised 14 group papers submitted at the end of an Indonesian Language course in the 2024/2025 academic year: seven papers from Class A and seven from Class C. Each paper was evaluated on five dimensions reported in the source dataset: language use, thematic relevance, organization, presentation/neatness, and references. Descriptive statistics were recalculated from the paper-level scores. The overall mean was 81.07 (SD = 2.30), with Class A averaging 80.57 and Class C 81.57. Ten of the 14 papers (71.43%) were classified as good and four (28.57%) as fair; all papers met the study's minimum passing criterion of 75. Presentation/neatness was the strongest dimension (M = 85.00), whereas organization (M = 78.21) and language use (M = 78.57) were the weakest. Qualitative observations in the original dataset further indicated recurring difficulties in academic conventions, including punctuation and spelling, systematic organization, formatting consistency, citation practice, and limited use of scholarly sources. The findings suggest that first-year students can produce acceptable academic papers, but their performance remains transitional rather than fully proficient. Explicit genre instruction, transparent rubrics, scaffolded source-use practice, reference-management training, and iterative feedback are recommended. Because the analyzed texts were group products and the original scoring instrument lacked reported inter-rater reliability, the findings should be interpreted as a profile of paper quality rather than a direct measure of individual writing competence.